Landfill Site Selection Using GIS Based Multicriteria Evaluation Technique in Harar City, Eastern Ethiopia - Elsai Mati Asefa; Yohannes Tefera Damtew; Kefelegn Bayu Barasa (SAGE Publishing, 2021)
Solid waste disposal is one of the challenging components in integrated solid waste management. Particularly the problem is prominent in cities with rapid population growth and waste generation. Harar, a capital city of Harari regional state located in the eastern part of Ethiopia, covers an area of 19.5 km 2 and has a total population of 270 000. Despite the fastest population growth of the city, it doesn't have a landfill site to accommodate the waste generated and open dumping is in full practice. As an integral part of a solid waste management plan, the construction of a landfill has been suggested by the city municipality. However, the multi-dimensional and conflicting aspect of landfill sitting, which involves environmental, social, technical, and economic considerations, challenges the location of a suitable landfill site. In the current study, we have applied geographic information system (GIS) and analytical hierarchy process (AHP) multi-criteria decision analysis to select a landfill site through minimizing conflicting interests. Environmental and socio-economic factors including well water, distance from residence, land use and land cover, elevation, slope, and wind direction were weighted to develop a suitability index for landfill siting. Experts' opinion was obtained to rank the aforementioned factors. The required landfill size was determined based on population growth, waste generation rate, and waste volume/year. Accordingly, the suitability index resulted in 3% of the area as highly suitable, and the rest 0.29%, 14.18%, 52.75%, and 29.8% classified as unsuitable, least suitable, moderately suitable, and suitable, respectively. Considering the future trend of waste generation, 16 ha of land located in the eastern part of the city was selected as a candidate landfill site with all the required suitability. The results of this study can be used as an input for decision making in siting landfill for Harar city.